Implementasi Ovitrap Sebagai Upaya Pencegahan DBD Di Desa Hajimena, Lampung Selatan - Agung Aji Perdana; Dina Dwi Nuryani; Angga Bayu Santoso; Muhammad Putra Pratama; Maharani Kartini (FKM UIN Sumatera Utara Medan, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the public health issues that needs to be watched out for, especially in areas with high population density. One simple, inexpensive, and effective vector control effort is the use of ovitraps as traps for Aedes aegypti mosquito eggs. This community service program was implemented in Hajimena Village with the aim of increasing residents' understanding and skills in making and utilizing ovitraps as a preventive measure against DHF. The methods used included socialization, practical training in making ovitraps, installation at mosquito breeding sites, and monitoring for four weeks. The participants consisted of 33 residents, cadres, and village health workers. The results of the activity showed a 14.58% increase in residents' knowledge based on pre- and post-tests, as well as an increase in skills in making ovitraps. These findings prove that ovitraps not only function as a means of vector control but are also effective as an applicable, inexpensive, and sustainable educational medium. Therefore, this program is expected to be widely implemented as a community empowerment strategy in dengue fever prevention efforts.